Poul Tuxen: Stege 1500-1950, Scandinavian Atlas of Historic Towns no. 5. (Danish Committee for Urban History. Odense University Press, 1987). 56 s. og 24 pl., 200 kr. (150 kr. i abonnement). - Grau Møller, Per (Historie/Jyske Samlinger, 1989)
-